Analisis Strategi Peningkatan Produksi Mebel di CV. Mustika Agung - Agun Syahrul Frastyansyah; Bima Tri Aji; Bagas Tri Mardiansyah; Aloysius Tommy Hendrawan (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
The purpose of the study is to create an appropriate marketing strategy for CV. Mustika Agung, a furniture craftsman in Magetan Regency. Primary data collected in this study were collected through interview methods. The results of the SWOT analysis of CV. Mustika Agung show that the formulation of a marketing strategy requires changes in the market, product design, production process, and advertising and marketing. This study will help solve the problems that exist in CV. Mustika Agung so that the resulting strategy will help the company survive and grow